Justice pursued - British Broadcasting Corporation. Television Service; Films for the Humanities (Firm); Fulcrum (Firm) (Princeton, N.J. : Films for the Humanities & Sciences, 1998)
"Rwanda, Argentina, East Germany and Bosnia have been the locus for the most heinous acts of the last 20 years. Gerald Gahima, Rwanda's Minister of Justice, has the job of tracking down hundreds of Rwandans accused of perpertrating hideous atrocities against their neighbors. He receives advice on how to proceed from a former Nazi-hunter. The torture and murder of thousands of young Argentines by the Pinochet regime are detailed by a survivor. In East Germany, newly discovered Stasi training tapes paint a brutal portrait of political repression, while in Bosnia, efforts to track down the perpetrators of ethnic cleansing are ongoing"--Container.
Originally released in 1997.
Directors, Jane Dibblin, Paul Mitchell, Michael Stewart ; producer, Michael Stewart ; series producer, Beth Holgate.
Narrator, Jeremy Harding.
VHS.
Keywords: Crimes against humanity; Genocide; Human rights; Political persecution